Analysis of Function Groups in Manihot esculenta and Hedyotis corymbosa Extracts Using Fourier Transform Infrared (FTIR) as Potential Immunomodulators - Rusyda, Tafdila Faza; Hildania, Ellya Putri; Lusiana, Nova; Agustina, Eva; Purnamasari, Risa; Hidayati, Irul; Andiarna, Funsu (International Conference on Sustainable Health Promotion, 2025)
Immunomodulators are substances that can help improve immune system function. Immunomodulators are clinically used for the treatment of immune disorders, such as cancer, HIV/AIDS, malnutrition, allergies and others. The use of synthetic drugs is effective in restoring immune system imbalances, but is at risk of causing side effects, so the search for safer natural alternatives is important. Cassava leaves (Manihot esculenta) and pearl grass (Hedyotis corymbosa) are plants rich in bioactive compounds, such as flavonoids, saponins, and triterpenoids, which have potential as immunomodulators. The mechanism of immunomodulation is thought to be through suppression of proinflammatory cytokines (TNF-α, IL-6, IL 1β, IL-17) and an increase in anti-inflammatory cytokines (IL-4, IL-10), while the effect on IL-2 is variable and IFN-γ tends to be lowered, thus supporting the achievement of a balanced immune response. This study aims to analyze the functional groups in Manihot esculenta and Hedyotis corymbosa extracts using Fourier Transform Infrared (FTIR) as a potential immunomodulator. The extracts were obtained through maceration method with 96% ethanol. The analysis showed that both extracts have main functional groups OH (alcohol/phenol), C=O (carbonyl), and CH (alkane) that support immunomodulatory activity. Hedyotis corymbosa extract showed a higher concentration of bioactive compounds, which could potentially provide a stronger immunomodulatory effect compared to Hedyotis corymbosa extract.